In-situ polymerization modified polymer solid electrolyte, preparation method thereof, diaphragm-free lithium secondary battery and lithium secondary battery

By introducing unsaturated nitrile monomers into high polymer materials and polymerizing in situ to form nitrile polymers, the problems of low conductivity and narrow electrochemical window of traditional polymer solid electrolytes are solved, and electrolytes with high conductivity, wide electrochemical window and good mechanical properties are achieved, and electrolytes are suitable for lithium secondary batteries with high voltage positive electrodes.

CN119920971APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD

Patent Information

Application Number
CN202411424613.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional polymer solid electrolytes have low ionic conductivity and narrow electrochemical windows, making them difficult to be suitable for high voltage positive electrodes.

Method used

Unsaturated nitrile monomers with specific structures are introduced into high polymer materials and in-situ polymerization is carried out to form nitrile polymers, improving conductivity and mechanical properties, while broadening the electrochemical window.

Benefits of technology

It improves the ion conductivity and mechanical properties of polymer solid electrolytes, and broadens the electrochemical window, so that it can match high voltage positive electrodes, improving the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081801250000171
    Figure BDA0005081801250000171
Patent Text Reader

Abstract

The invention provides an in-situ polymerization modified polymer solid electrolyte, a preparation method thereof, a diaphragm-free lithium secondary battery and a lithium secondary battery. The polymer solid electrolyte comprises a nitrile polymer as a component (A), a polymer matrix as a component (B) and a lithium salt as a component (C), wherein the component (A) nitrile polymer is derived from an unsaturated nitrile monomer; the unsaturated nitrile monomer comprises an unsaturated aliphatic compound with a cyano group substitution; the unsaturated aliphatic compound contains more than three carbon atoms; the unsaturated nitrile monomer contains at least one unsaturated group, and the component (A) is polymerized in situ in the solid electrolyte. According to the invention, unsaturated nitrile monomers with specific structures are introduced into a high polymer material, and the unsaturated nitrile monomers are polymerized in the high polymer material in situ. Through the nitrile polymer with the specific structure, the ionic conductivity and the mechanical property of the polymer solid electrolyte are improved, and the electrochemical window of the polymer solid electrolyte is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an in-situ polymerization-modified polymer solid electrolyte, a preparation method thereof, a diaphragm-free lithium secondary battery and a lithium secondary battery, belonging to the technical field of lithium ion batteries. Background Art

[0002] Polymer solid electrolytes have become one of the important technical routes for the next generation of all-solid-state batteries due to their excellent processing performance, low cost, good interface compatibility, and environmental friendliness. Common polymer solid electrolytes include PEO (polyethylene oxide), PAN (polyacrylonitrile), polyvinylidene fluoride (PVDF), etc. At present, all-solid-state batteries based on PEO-based polymer electrolytes have been used in mining cars, buses, special vehicles and other fields. However, due to the low ionic conductivity of PEO-based polymer electrolytes at room temperature, when using batteries with PEO-based polymer electrolytes, they often need to be heated to above 60°C to work normally. In addition, the electrochemical window of PEO-based polymer solid electrolytes is narrow, and it is difficult to match high-voltage positive electrode materials such as ternary material positive electrodes, which limits their application.

[0003] At present, the main methods to improve electrical conductivity include grafting, blending, copolymerization, and adding inorganic fillers.

[0004] Some literature discloses a carbonate polymer electrolyte, which has a room temperature ionic conductivity of 2×10 -5 S / cm~1×10 -4 S / cm, and the electrochemical window is greater than 4 V. However, electrolytes containing carbonate bonds are easily reduced on the surface of the metallic lithium negative electrode, which not only reduces the coulombic efficiency, but also easily leads to the formation of lithium dendrites during the charge and discharge process, affecting the safety of use.

[0005] In addition, for lithium-ion batteries, a diaphragm may or may not be used in its structure. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. In the case of using a diaphragm, the main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. In the case of not using a diaphragm, the positive and negative electrodes are usually separated by the electrolyte itself to prevent short-circuiting, and ions are conducted by the electrolyte itself. From the perspective of the energy density of lithium secondary batteries, secondary batteries without diaphragms are advantageous. In particular, the use of solid electrolytes (such as quasi-solid or all-solid electrolytes) makes diaphragm-free batteries possible.

[0006] It can be seen that although a series of studies have been conducted in this field on the improvement of polymer solid electrolytes, there is still room for further improvement in the development of polymer solid electrolytes with both high ionic conductivity and wide electrochemical window. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] In order to address the problem that traditional polymer solid electrolytes have low ionic conductivity and narrow electrochemical window and are not suitable for high-voltage positive electrodes, the modification methods mainly include blending, copolymerization or adding inorganic fillers with organic polymers.

[0009] In the method of blending and copolymerization with organic polymers, it is usually difficult to solve the problems of low ion conductivity and narrow electrochemical window at the same time by polymerization modification of a single small molecule monomer. However, the addition of multiple small molecule monomers will make the structure and degree of polymerization after polymerization, experimental repeatability, etc. more difficult to control and the cost is high. In the method of adding organic fillers, there are often problems such as uneven mixing, easy agglomeration, and blocking of lithium ion migration channels.

[0010] Furthermore, as a previous research result of the applicant, in the Chinese patent application with application number 202410670877.5, in-situ polymerization was used to improve the performance of the final electrolyte. Although this achievement has aroused some interest in the subsequent in-situ polymerization modification route of the applicant, however, in the subsequent specific practice, it was also found that even if the in-situ polymerization method is adopted, the result is strongly dependent on the type of monomer. This is mainly due to the differences in compatibility, flexibility / crystallization, ion coordination, electrochemical window performance, voltage resistance / heat resistance, etc. between different monomers and their polymers. For example, many polar monomers are not suitable for this polymerization route, resulting in phase separation after in-situ polymerization, or the product of in-situ polymerization cannot achieve the required ion conductivity, stability and other requirements in electrical testing. Therefore, for the desired performance improvement, the type of monomer still needs to be selected very carefully.

[0011] In order to solve the above problems, based on further research, the present invention provides a polymer solid electrolyte modified by in-situ polymerization and a preparation method and application thereof, wherein the polymer solid electrolyte is prepared by introducing an unsaturated nitrile monomer of a specific structure into a high polymer material (such as PVDF, PEO, PMMA, PAN, etc.) and polymerizing the monomer in-situ in the high polymer material. The nitrile polymer of the specific structure not only improves the ion conductivity and mechanical properties of the polymer solid electrolyte, but also broadens its electrochemical window, and does not have problems in processability.

[0012] Furthermore, the present invention also provides a method for preparing a polymer solid electrolyte, which can improve the interface compatibility and mechanical properties of each component in the polymer solid electrolyte, make each polymer component fully compatible, further improve the lithium ion transmission capacity and widen the electrochemical window.

[0013] Furthermore, the present invention also provides a lithium secondary battery, which comprises the polymer solid electrolyte described above or the polymer solid electrolyte prepared by the preparation method described above.

[0014] Solutions for solving problems

[0015] The present invention first provides an in-situ polymerized modified polymer solid electrolyte, wherein the polymer solid electrolyte comprises a nitrile polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C);

[0016] Wherein, the nitrile polymer of component (A) is derived from unsaturated nitrile monomers:

[0017] The unsaturated nitrile monomers include unsaturated aliphatic compounds having one cyano substitution;

[0018] Furthermore, the unsaturated aliphatic compound contains more than 3 carbon atoms; the unsaturated nitrile monomer contains at least one unsaturated group,

[0019] The component (A) is polymerized in situ in the solid electrolyte.

[0020] According to the polymer solid electrolyte of the present invention, the unsaturated aliphatic compound contains 3 to 15 carbon atoms.

[0021] According to the polymer solid electrolyte of the present invention, the unsaturated aliphatic compound is further substituted by one or more F atoms.

[0022] According to the polymer solid electrolyte of the present invention, the unsaturated nitrile monomer contains 1 to 3 unsaturated groups.

[0023] According to the polymer solid electrolyte of the present invention, the unsaturated group is an alkenyl group.

[0024] According to the polymer solid electrolyte of the present invention, the unsaturated nitrile monomer includes a combination of one or more of 2-butenenitrile, 5-hexenenitrile and limononitrile.

[0025] According to the polymer solid electrolyte of the present invention, the mass ratio of the component (A) to the component (B) is 1:10 to 1:20.

[0026] According to the polymer solid electrolyte of the present invention, the component (B) polymer matrix comprises a fluorine-containing polymer.

[0027] According to the polymer solid electrolyte of the present invention, the component (B) polymer matrix includes one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polyethylene oxide, polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyurethane, polyurea, polyvinyl pyrrolidone, polyvinyl chloride, polypropylene carbonate, polyimide, nylon, polyethylene terephthalate, poly-2-vinyl pyridine, poly-4-vinyl pyridine, etc.

[0028] In addition, the present invention also provides a method for preparing the in-situ polymerization-modified polymer solid electrolyte according to the present invention, which comprises the following steps:

[0029] The polymer matrix, lithium salt, unsaturated nitrile monomer and initiator are mixed in an organic solvent to obtain a mixed solution;

[0030] The unsaturated nitrile monomer is subjected to a polymerization reaction.

[0031] According to the preparation method of the present invention, the mass ratio of the unsaturated nitrile monomer to the polymer matrix is ​​1:10 to 1:20;

[0032] The amount of the initiator is 0.01% to 1% by mass of the unsaturated nitrile monomer;

[0033] The amount of the lithium salt used is 10% to 80% by mass of the sum of the mass of the polymer matrix, the lithium salt and the unsaturated nitrile monomer.

[0034] In addition, the present invention also provides a diaphragm-free lithium secondary battery, wherein the diaphragm-free lithium secondary battery comprises a positive electrode, a negative electrode, and comprises or uses the polymer solid electrolyte described in the present invention or the polymer solid electrolyte obtained according to the preparation method of the present invention.

[0035] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery comprises a positive electrode, a negative electrode, a separator, and comprises or uses the polymer solid electrolyte described in the present invention or the polymer solid electrolyte obtained according to the preparation method described in the present invention.

[0036] Effects of the Invention

[0037] 1) The polymer solid electrolyte provided by the present invention introduces a nitrile polymer, wherein the cyano functional group has a synergistic effect with the existing functional groups in the polymer matrix, which can effectively improve the ionic conductivity of the polymer solid electrolyte. At the same time, the cyano group, as a strong polar group, can effectively broaden the electrochemical window of the polymer solid electrolyte, so that it can match the high-voltage positive electrode.

[0038] 2) The preparation method of the composite polymer solid electrolyte provided by the present invention introduces small molecule monomers into the polymer matrix solution and directly performs in situ polymerization in the solution, so that the two polymer molecular chains can be fully compatible, entangled, and form an interpenetrating network structure, thereby inhibiting the crystallinity of the polymer matrix at room temperature, enhancing the movement of chain segments, and further improving the lithium ion transmission capacity.

[0039] 3) The nitrile polymer provided by the present invention can be formed by polymerizing only one unsaturated nitrile monomer, which can bring convenience in operation and cost.

[0040] 4) In some specific embodiments, when the unsaturated nitrile monomer contains two or more carbon-carbon double bonds, it is more conducive to forming a cross-linked structure, promoting the formation of an interpenetrating network between the polymer matrix material and the nitrile polymer molecular chain formed by in situ polymerization, thereby further inhibiting the crystallization ability of the polymer matrix and improving the lithium ion transmission capacity.

[0041] 5) In addition, selecting nitrile compounds with appropriate structures can alleviate the problems of high structural rigidity and high glass transition temperature of polymers. DETAILED DESCRIPTION

[0042] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0043] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0044] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0045] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0046] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0047] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0048] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0049] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0050] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0051] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0052] The present invention mainly provides an in-situ polymerization-modified polymer solid electrolyte and a preparation method thereof. By introducing unsaturated nitrile monomers into a traditional polymer matrix material and performing in-situ polymerization to modify the polymer matrix material, the ionic conductivity of the polymer solid electrolyte is improved while the mechanical strength is improved and the electrochemical window is widened, so that it can match a high-voltage positive electrode.

[0053] The present invention is mainly obtained through the following insights:

[0054] As mentioned above, the previous methods of forming polymer electrolytes by blending and copolymerization modification have many shortcomings.

[0055] Furthermore, it has been found that, although nitrile polymers have a high polarity, on the one hand, such polymers generally have a high rigidity structure and a high glass transition temperature, which is disadvantageous for applications.

[0056] Through the research of the present invention, it has been found that by introducing unsaturated nitrile monomers with strong polar cyano groups of specific structures into traditional polymer matrix materials and modifying the polymer matrix materials by in-situ polymerization, the above-mentioned problems in the application of nitrile polymers can be overcome, and the problems of existing modified polymer electrolytes can also be avoided.

[0057] On the one hand, the in-situ fusion of high-rigidity nitrile polymers with polymer matrices with lower hardness (such as PVDF, PEO, PMMA, PAN, etc.) also reduces the adverse effects of the high rigidity of nitrile polymers.

[0058] On the other hand, the present invention also found that in the preparation of polymer solid electrolytes, the adverse effects caused by interface compatibility have a great impact on the electrochemical stability of polymer solid electrolytes. Therefore, the present invention introduces small molecule monomers into the polymer matrix solution and directly performs in situ polymerization in the solution, so that the two polymer molecular chains can be fully compatible, entangled, and form an interpenetrating network structure, thereby effectively improving the interface compatibility of the components in the polymer solid electrolyte. In addition, the interpenetrating network can also inhibit the crystallinity of the polymer matrix at room temperature, enhance the movement of chain segments, and further improve the lithium ion transmission capacity and mechanical properties.

[0059] Therefore, the prepared polymer solid electrolyte membrane can not only improve the lithium ion transportability, but also broaden the electrochemical window to match high voltage, and can also effectively suppress the problems caused by lithium dendrites and improve the cycle stability of the battery.

[0060] <First aspect>

[0061] A first aspect of the present invention provides an in-situ polymerized modified polymer solid electrolyte, the polymer solid electrolyte comprising a nitrile polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C).

[0062] In addition, various functional additive components may be used in the polymer solid electrolyte composition without hindering the realization of the technical effects of the present invention.

[0063] Component (A)

[0064] The nitrile polymer as component (A) described in the present invention is derived from an unsaturated nitrile monomer, and the unsaturated nitrile monomer includes an unsaturated aliphatic compound having a cyano group substitution, wherein the unsaturated aliphatic compound can be a linear or branched unsaturated aliphatic compound.

[0065] As for the number of nitrile groups, it has been found that, due to their high polarity, if the number of nitrile groups exceeds 1, the compatibility of the final polymer with the polymer matrix as component (B) described below may deteriorate, and phase separation may occur. At the same time, too many nitrile groups may also cause the polymer chain segments obtained by polymerization to be too rigid, which is not conducive to the conduction of lithium ions.

[0066] Furthermore, the unsaturated aliphatic compound may have more than 3 carbon atoms. When the number of carbon atoms is too small, the polarity of the nitrile polymer may be too strong, thereby causing concerns about poor compatibility with the polymer matrix. From the perspective of adjusting polarity and polymer rigidity, in some preferred embodiments, the unsaturated aliphatic compound contains 3 to 15 carbon atoms, such as 5, 7, 9, 11, 13, etc.

[0067] In addition, the unsaturated aliphatic compound may further have a substituent other than the nitrile group. Such a substituent is preferably a fluorine atom in view of compatibility and polarity.

[0068] The unsaturation degree of the unsaturated nitrile monomer may generally be 1 to 3, that is, each unsaturated aliphatic compound may have 1 to 3 polymerizable / unsaturated groups, and such groups may preferably be free-radically polymerizable double bonds.

[0069] In some specific embodiments, the unsaturated nitrile monomer has a linear aliphatic structure, and has at least one double bond in the linear chain, for example, 1, 2 or 3 double bonds. In some other specific embodiments, the unsaturated nitrile monomer has a branched aliphatic structure, and has at least one double bond in the branched portion.

[0070] The unsaturated nitrile monomer is polymerized in situ through an unsaturated carbon-carbon double bond to form a nitrile polymer, which forms a molecular chain entanglement with the polymer matrix, disrupts the orderly arrangement of the polymer matrix molecules, inhibits its crystallinity at room temperature, enhances the movement of the chain segments, and improves the transmission capacity of lithium ions. In some preferred embodiments, the unsaturated nitrile monomer contains two or more carbon-carbon double bonds that can be polymerized by free radicals. When the unsaturated nitrile monomer contains more than two carbon-carbon double bonds, it is more conducive to forming a cross-linked structure, promoting the formation of an interpenetrating network between the polymer matrix material and the nitrile polymer molecular chain formed by in situ polymerization, thereby further inhibiting the crystallization ability of the polymer matrix and improving the transmission capacity of lithium ions.

[0071] In some more preferred embodiments, the unsaturated nitrile monomers specifically include 2-butenenitrile, 5-hexenenitrile, lemon nitrile and the like.

[0072] As for the unsaturated nitrile monomer of the present invention, only one kind may be used, or a plurality of kinds may be used simultaneously when necessary.

[0073] In addition, in addition to the above-mentioned unsaturated nitrile monomers, other unsaturated monomers can also be used in component (A) of the present invention. When other unsaturated monomers are used, these monomers account for less than 10% by mass of the total mass of all monomers, preferably less than 8% by mass, and more preferably less than 5% by mass.

[0074] Component (B)

[0075] The polymer matrix as component (B) in the present invention is provided as a base material.

[0076] The type of polymer matrix may be a high molecular polymer material. These polymer materials usually have a higher dielectric constant, which can make the lithium salt described below ionized better. In addition, since nitrile polymers may have the characteristics of a high glass transition temperature, they are in a glassy state at room temperature, and the molecular chain segments are difficult to move. In order to reduce the glass transition temperature of the polymer solid electrolyte, the polymer matrix needs to have a lower glass transition temperature to promote the molecular chain movement at room temperature.

[0077] In some specific embodiments of the present invention, such a polymer matrix can be selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polyethylene oxide (PEO), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (PVDF-TrFE-CTFE), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), polyvinyl chloride (PVC), polypropylene carbonate (PPC), etc.

[0078] In some preferred embodiments, the polymer matrix may include a fluorine-containing polymer, which may further promote the compatibility and synergy between the polymer matrix and the nitrile polymer.

[0079] Component (C)

[0080] The lithium salt as component (C) described in the present invention is the source of active ions in the polymer solid electrolyte and is included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.

[0081] In some specific embodiments, the lithium salt can be selected from one or more salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2- 、C(CF2SO2)3 - 、C2BF2O4 - wait.

[0082] In some preferred embodiments, the lithium salt may be selected from a combination of one or more of lithium hexafluorophosphate (LiPF6) or lithium bis(fluorosulfonyl)imide (LiFSI).

[0083] Composition of polymer solid electrolyte

[0084] Regarding the composition of the polymer solid electrolyte of the present invention, from the aspect of improving the electrical properties of the electrolyte, the content of each component of the present invention can be arranged as follows:

[0085] The mass ratio of component (A) to component (B) is 1:8 to 1:25, preferably 1:10 to 1:20, more preferably 1:10 to 1:15, such as 1:11, 1:13, 1:15, 1:17, 1:19, etc. If the content of component (A) is too low, it will not have the corresponding effects of inhibiting crystallization, improving the electrochemical window of the polymer electrolyte, sufficient cross-linking, and strong interaction between functional groups; if the content of component (A) is too high, the glass transition temperature of the polymer solid electrolyte may be higher, and at this time, there may be a certain selectivity for the applicability of the polymer matrix.

[0086] The amount of the component (C) is not particularly limited in principle, and can be carried out in accordance with the general specifications of the amount of lithium salts in the art. In some specific embodiments, the content of the component (C) is 10% to 80% by weight of the sum of the weights of the components (A), (B) and (C), preferably 30% to 40% by weight, such as 20%, 30%, 40%, 50%, 60%, 70% by weight, etc. If the content of component (C) is too low, the lithium ion transmission capacity will be reduced; if the content of component (C) is too high, it will lead to an unnecessary increase in cost and may also affect the mechanical properties of the polymer solid electrolyte.

[0087] The (usage) form of polymer solid electrolyte

[0088] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the above-mentioned polymer solid electrolyte composition can be provided separately as an independently supported membrane, and in other specific embodiments, it can be provided integrally with the positive and negative electrode sheets.

[0089] In some specific embodiments, the polymer solid electrolyte obtained by the present invention substantially does not contain organic solvent or (at room temperature) liquid electrolyte.

[0090] <Second Aspect>

[0091] The second aspect of the present invention provides a method for preparing the in-situ polymerization-modified polymer solid electrolyte according to the first aspect.

[0092] The preparation method of the present invention comprises:

[0093] The polymer matrix, lithium salt, unsaturated nitrile monomer and initiator are mixed in an organic solvent to obtain a mixed solution;

[0094] The unsaturated nitrile monomer is subjected to a polymerization reaction.

[0095] The types and amounts of the polymer matrix, lithium salt, and unsaturated nitrile monomer are the same as those in the first aspect and will not be described in detail herein.

[0096] The initiator described in the present invention is a free radical initiator, which is used to cause the unsaturated nitrile monomer to undergo free radical polymerization in the polymer matrix to form a cross-linked network.

[0097] The free radical initiator can be a thermal initiator or a photoinitiator.

[0098] The type of thermal initiator may be selected from one or more of azo initiators, organic peroxide initiators and the like.

[0099] In some specific embodiments, the thermal initiator may include one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, dibenzoyl peroxide, diethylhexyl peroxydicarbonate, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxycarbonate, potassium persulfate, or ammonium persulfate.

[0100] The type of photoinitiator can be selected from one or more of the cleavage type or the hydrogen abstraction type. In some specific embodiments, the cleavage type can be selected from one or more of benzoin and its derivatives, acetophenones, aromatic ketones and acylphosphine oxides; the hydrogen abstraction type initiator can be selected from one or more of benzophenone, thioxanthone, camphor porquinone and bisimidazole.

[0101] Regarding the amount of the initiator added, the amount of the initiator added is 0.01% to 1% by mass of the unsaturated nitrile monomer, preferably 0.2% to 0.5% by mass, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, etc. The amount of the initiator used can be used to control the nitrile polymer to have a suitable degree of polymerization.

[0102] In principle, there is no particular restriction on the type of organic solvent, and for example, it can be selected from at least one of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0103] In some specific embodiments, in the mixing step, in order to achieve the migration of lithium ions, the polymer substrate and the lithium salt can be first mixed with the organic solvent and stirred thoroughly until dissolved to dissociate the lithium salt, and then the unsaturated nitrile monomer and the initiator can be added.

[0104] In addition, the polymerization reaction may be controlled by, for example, irradiating or heating the polymerization reaction.

[0105] In some specific embodiments, the polymerization reaction may be caused by heating when a thermal initiator is used. There is no particular limitation on the reaction temperature, and the required reaction temperature may be used according to the type of initiator. In some preferred embodiments, the reaction temperature may be 40 to 70°C, such as 45°C, 50°C, 55°C, 60°C, 65°C, etc.; the reaction time may be 4 to 18 hours, such as 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.

[0106] In some more specific embodiments, the reaction can be carried out under inert gas conditions, such as argon, etc. Specifically, after the mixing step, an inert gas can be introduced into the mixed solution to expel the air dissolved in the solvent and in the reaction container, and the mixture is sealed.

[0107] In other specific embodiments, free radicals can be formed and polymerization of monomers can be initiated by ultraviolet light irradiation when a photoinitiator is used. The polymerization reaction time can be several minutes. The advantages of photoinitiated polymerization are fast polymerization speed, less solvent volatilization, environmental friendliness, low cost, low energy consumption, etc.

[0108] In some specific embodiments, the preparation method further comprises a film-forming step, and the film-forming method may be a solution coating method, an extrusion casting method or the like.

[0109] In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. There is no particular limitation on the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, for example, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e., removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte sheet of Φ16mm.

[0110] The preparation method of the present invention has many advantages such as low cost, simple method, environmental friendliness, and high safety of the prepared polymer solid electrolyte, and has extremely broad prospects in practical application.

[0111] <Third Aspect>

[0112] The third aspect of the present invention provides a lithium secondary battery, in particular a lithium secondary battery comprising or using the polymer solid electrolyte of the first aspect of the present invention or a polymer solid electrolyte prepared according to the preparation method described in the second aspect.

[0113] Such a lithium secondary battery at least includes a positive electrode, a negative electrode and a solid electrolyte. In addition, a diaphragm can be used when necessary. In some specific embodiments, a diaphragm is further used in the lithium secondary battery. There is no particular restriction on such a diaphragm, and an organic porous membrane can be used. In some other specific embodiments, the lithium secondary battery is a diaphragm-free lithium secondary battery. Preferably, the lithium secondary battery can be an all-solid-state battery, which is allowed to not contain a liquid electrolyte and a diaphragm, and relies on a solid electrolyte to isolate the positive and negative electrodes and transmit lithium ions.

[0114] For the positive electrode in the lithium secondary battery, a high-voltage oxide positive electrode material for lithium-ion batteries can be used, such as lithium cobalt oxide (LCO), lithium nickel manganese oxide (LNMO), and high-nickel content ternary positive electrode (6 series, 8 series) materials (such as NCM811, NCA622, etc.).

[0115] There is no particular limitation on the negative electrode, which may be a common negative electrode for solid polymer batteries. Preferably, the negative electrode is a lithium negative electrode.

[0116] Example

[0117] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0118] Example 1

[0119] Preparation of polymer solid electrolyte solution:

[0120] Dissolve 10 g PVDF, 5.5 g lithium bis(trifluoromethanesulfonyl)imide (equivalent to 50% of the total mass of all polymers after polymerization) and 0.005 g AIBN in 30 ml DMF and stir magnetically until dissolved. Add 1 g 2-butenenitrile and continue mixing for 30 min. Then, introduce inert gas for 30 min to expel the air in the container, and then heat to 65 °C and stir for 4 h.

[0121] Preparation of composite solid polymer electrolyte membrane:

[0122] The mixed solution prepared above was poured onto a clean glass plate and dried in a vacuum drying oven at 80°C for 8 hours using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular electrolyte sheet.

[0123] The polymer solid electrolyte sheet prepared above was used for battery assembly and testing, as shown in Table 1.

[0124] Example 2

[0125] The difference from Example 1 is that 2-butenenitrile is replaced by citronellium, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0126] Example 3

[0127] The difference from Example 1 is that PVDF is replaced by PVDF-HFP, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0128] Example 4

[0129] The difference from Example 1 is that PVDF is replaced by PVDF-CTFE, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0130] Example 5

[0131] The difference from Example 1 is that the amount of 2-butenenitrile added is 0.8 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0132] Example 6

[0133] The difference from Example 1 is that the amount of 2-butenenitrile added is 0.7 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0134] Example 7

[0135] The difference from Example 1 is that the amount of 2-butenenitrile added is 0.6 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0136] Example 8

[0137] The difference from Example 1 is that the amount of 2-butenenitrile added is 0.5 g, and the remaining steps are the same as Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0138] Example 9

[0139] Preparation of polymer solid electrolyte solution:

[0140] 10 g of PVDF, 5.5 g of lithium bis(trifluoromethanesulfonyl)imide (equivalent to 50% of the total mass of all polymers after polymerization) and 0.005 g of benzophenone were dissolved in 30 ml of DMF and magnetically stirred until dissolved. 1 g of 2-butenenitrile was added and the mixture was mixed for 30 min. An inert gas was introduced for 30 min to exhaust the air in the container. The container was exposed to ultraviolet light for 20 min under magnetic stirring.

[0141] Preparation of composite solid polymer electrolyte membrane:

[0142] The mixed solution prepared above was poured onto a clean glass plate and dried in a vacuum drying oven at 80°C for 8 hours using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular electrolyte sheet.

[0143] The polymer solid electrolyte sheet prepared above was used for battery assembly and testing, as shown in Table 1.

[0144] Comparative Example 1

[0145] The difference from Example 1 is that the mixed solution is not heated, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared, and a battery is assembled to perform subsequent ion conductivity tests. The details are shown in Table 1.

[0146] Comparative Example 2

[0147] The difference from Example 1 is that 2-butenenitrile is not added, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is prepared, and a subsequent ion conductivity test is performed after assembling into a battery.

[0148] Comparative Example 3

[0149] The difference from Example 1 is that the added polymer monomer is methyl methacrylate, and the other steps are the same.

[0150] Performance Testing

[0151] 1. Ionic conductivity: The polymer solid electrolyte membrane (CSEs) prepared above was combined with two stainless steel electrodes (SS) to form a SS / CSEs / SS simulated battery for testing. The battery assembly process was carried out in a glove box with a water and oxygen content of less than 0.1ppm. The electrochemical impedance spectroscopy (EIS) test used a frequency range of 0.01Hz to 106Hz to measure the electrochemical impedance of the polymer solid electrolyte at room temperature. The impedance data obtained from the EIS test was used to calculate the ionic conductivity of the prepared polymer solid electrolyte.

[0152] 2. Electrochemical window: Assemble stainless steel sheets to metal lithium sheet batteries with polymer solid electrolyte in the middle and use linear sweep voltammetry (LSV) for testing.

[0153] 3. Mechanical properties: Cut a 20 mm wide polymer solid electrolyte membrane material and test its tensile strength using a universal tensile testing machine at a loading rate of 30 mm / min.

[0154] Table 1 Performance test results of embodiments and comparative examples

[0155]

[0156] The results of Examples 1-2, 5-9 and Comparative Example 2 show that the introduction of nitrile polymers can effectively improve the ionic conductivity, mechanical properties and electrochemical window of polymer solid electrolytes.

[0157] The results of Examples 1 and 3-4 indicate that nitrile polymers are also compatible with different polymer substrates, exhibiting high ionic conductivity and a wide electrochemical window.

[0158] The results of Example 1 and Comparative Example 1 show that if only unsaturated nitrile monomers are added without initiating polymerization, the electrochemical performance of the polymer solid electrolyte cannot be significantly improved.

[0159] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0160] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. An in-situ polymerized modified polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises a nitrile polymer as component (A), a polymer matrix as component (B) and a lithium salt as component (C); Wherein, the nitrile polymer of component (A) is derived from unsaturated nitrile monomers: The unsaturated nitrile monomers include unsaturated aliphatic compounds having one cyano substitution; Furthermore, the unsaturated aliphatic compound contains more than 3 carbon atoms; the unsaturated nitrile monomer contains at least one unsaturated group, The component (A) is polymerized in situ in the solid electrolyte.

2. The polymer solid electrolyte according to claim 1, characterized in that The unsaturated aliphatic compound contains 3 to 15 carbon atoms.

3. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The unsaturated aliphatic compound is further substituted by one or more F atoms.

4. The polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The unsaturated nitrile monomer contains 1 to 3 unsaturated groups.

5. The polymer solid electrolyte according to claim 4, characterized in that: The unsaturated group is an alkenyl group.

6. The polymer solid electrolyte according to any one of claims 1 to 5, characterized in that: The unsaturated nitrile monomers include one or more of 2-butenenitrile, 5-hexenenitrile and lemon nitrile.

7. The polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: The mass ratio of the component (A) to the component (B) is 1:10 to 1:

20.

8. The polymer solid electrolyte according to any one of claims 1 to 7, characterized in that: The component (B) polymer matrix includes a fluorine-containing polymer.

9. The polymer solid electrolyte according to any one of claims 1 to 8, characterized in that: The component (B) polymer matrix includes one or more combinations of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polyethylene oxide, polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene copolymer, polyacrylonitrile, polymethyl methacrylate, polyurethane, polyurea, polyvinyl pyrrolidone, polyvinyl chloride, polypropylene carbonate, polyimide, nylon, polyethylene terephthalate, poly-2-vinyl pyridine, and poly-4-vinyl pyridine.

10. A method for preparing an in-situ polymerized modified polymer solid electrolyte according to any one of claims 1 to 9, characterized in that: The following steps are involved: The polymer matrix, lithium salt, unsaturated nitrile monomer and initiator are mixed in an organic solvent to obtain a mixed solution; The unsaturated nitrile monomer is polymerized.

11. The preparation method according to claim 10, characterized in that: The mass ratio of the unsaturated nitrile monomer to the polymer matrix is ​​1:10 to 1:20; The amount of the initiator is 0.01% to 1% by mass of the unsaturated nitrile monomer; The amount of the lithium salt used is 10% to 80% by mass of the sum of the mass of the polymer matrix, the lithium salt and the unsaturated nitrile monomer.

12. A diaphragm-free lithium secondary battery, characterized in that: The separator-free lithium secondary battery comprises a positive electrode, a negative electrode and comprises or uses the polymer solid electrolyte according to any one of claims 1 to 9 or the polymer solid electrolyte obtained by the preparation method according to claim 10 or 11.

13. A lithium secondary battery, characterized in that: The lithium secondary battery comprises a positive electrode, a negative electrode, a separator and comprises or uses the polymer solid electrolyte according to any one of claims 1 to 9 or the polymer solid electrolyte obtained by the preparation method according to claim 10 or 11.

Citation Information

Patent Citations

  • Polymer solid electrolyte, preparation method thereof and battery

    CN118630308A

Cited By

  • High-voltage chloride solid electrolyte with stable in-situ polyacrylonitrile flexible ion transmission interface layer and preparation method and application of high-voltage chloride solid electrolyte

    CN121123378A